Sistem Pakar Untuk Penyusunan Jadwal Kuliah Berbasis Forward Chaining - Feriani Astuti Tarigan (STMIK TIME, 2015)
Subject scheduling is a process of arranging exact time to avoid conflict with related rules such as lecturers, classroom, laboratories, and the subjects offered. Subject scheduling is arranged before each semester strated in order to avoid repeticion, in sekolah tinggi manajemen informatika dan komputer time,subject scheduling is made manually by staff. It is true that the process is difficiulty & is not timely difficult in this research, correct ruler are designed to avoid any conflict that may accurs. The description of the ruler are done by using forward chaining system